Blood at Sundown : the violent days of Lou Prophet, bounty hunter - Brandvold, Peter (Brandvold, Peter. Bounty hunter Lou Prophet series., 2019)
Bounty hunter Lou Prophet and Louisa, the dangerous woman he loves, pursue the Griff Hatchley Gang across the Dakota Territory and catch up with them as a blizzard hits, forcing them to split up in order to pursue their prey.